Anesthesia for pregnant patients with symptomatic neurological disease: 13 years’ experience from a tertiary care center - Stefano Catarci; Bruno Antonio Zanfini; Marco Scorzoni; Salvatore De Martino; Pietro Paolo Giuri; Luciano Frassanito; Gian Luigi Gonnella; Emanuele Capone; Francesco Vitale Di Maio; Giovanni Maddaloni; Antonio Lanzone; Gaetano Draisci (BMC Anesthesiology)
Abstract Background Improvements in diagnostics and clinical care have allowed more women of childbearing age, suffering from neurological diseases, to safely have pregnancy, reducing peripartum complications. However, these patients remain at risk and are a constant challenge for anesthesiologists in the delivery room. Methods To assess the type of anesthesiologic management performed for delivery in obstetric patients with preexisting neurological disease and who reported significant neurological symptoms during pregnancy, a retrospective observational study was carried out between 1 October 2008 and 30 September 2021. Results Data from 49,202 pregnant women were assessed over 13 years; 239 pregnant women with a diagnosis of preexisting neurological disease and who reported significant neurological symptoms during pregnancy were identified (prevalence 0.49%). The main neurological disorders that affected pregnant women included vascular abnormalities and intracranial bleeding (N = 42, 17.6%), central nervous system tumors (N = 35, 14.6%), epilepsy and episodic and paroxysmal disorders of the central nervous system (N = 34, 14.2%), diseases of the neuromuscular junction and muscles (N = 26, 10.9%), demyelinating central nervous system diseases (N = 24, 10%). A total of 234 (97.9%) pregnant women with neurological disorders and significant neurological symptoms underwent cesarean section: 192 (80.3% of the total cesarean sections) were elective, 39 (16.3%) were urgent type 2 and 3; 3 (1.2%) were emergency cesarean sections. General anesthesia was administered to 73 patients (30.5%), while 166 patients (69.5%) were managed with neuraxial techniques. 2 patients who had had neuraxial block reported worsening neurological symptoms that required a change in medical therapy. Postoperative multiparameter monitoring was performed for less than 24 h in the recovery room for 226 patients (94.6%). 3 patients (1.2%) were observed with multiparameter monitoring in the post-anesthesia care unit (PACU) for more than 24 hours; 10 patients (4.2%) were moved to the postoperative intensive care unit (ICU). The median hospitalization duration was 4 days (with an interquartile difference of 3–6 days). Conclusions In our experience, when neuraxial anesthesia was feasible, it proved to be a safe option for pregnant patients with symptomatic neurological disease, resulting in uncommon maternal complications.